L'analisi empirica della segmentazione e della flessibilità del lavoro utilizzando le tecniche di job creation e destruction - Giovanni Guidetti (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1999)
– The aim of this paper is to provide an empirical investigation of labour market segmentation and flexibility. For this purpose, the techniques based on the analysis of job creation and destruction ( see, Davis et al, 1996) have been used. The data analysed stem from a sample of manufacturing firms located in Emilia-Romagna and cover a period of eight years. This dataset allows to analyse the level of employment of both blue and white collars. The analysis shows in details the different dynamics of those two component of manufacturing employment. It is argued that white and blue collars can be considered as two different occupational sub-systems (see, Osterman 1982, 1984) and that internal la-bour market segmentation gives rise to divergent indicators of numerical flexibility for the two components of em-ployment.
Keywords: 330